2019
DOI: 10.1002/ieam.4208
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Contribution Made to Down‐the‐Drain Emissions of D5 by Personal Care Product Categories in the European Union

Abstract: Aquatic risk assessment of personal care chemicals requires quantifying the contribution of all product types containing these ingredients to down‐the‐drain emissions. We developed a probabilistic model framework embracing stochastic variability associated with individual consumers and their behaviors in the European Union, as well as other sources of uncertainty related to losses following applications (e.g., volatilization). The model was applied to decamethylcyclopentasoloxane (D5), an emollient used in was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This means that VMS have an opportunity to volatilize to the air before being washed off during showering (Gouin et al, 2013 ; Montemayor et al, 2013 ). Other products, such as shampoos, conditioners, and shaving products, are likely to be washed off immediately and make a bigger contribution to the wastewater load (Franco & van Egmond, 2020 ). Monitoring data presented by van Egmond et al ( 2013 ) suggested that the Brooke et al ( 2009a ) estimate load estimates for D5 to wastewater (11.6 mg cap ⁻¹ day ⁻¹ ) may be overestimated by as much as a factor of 4.…”
Section: Emissionsmentioning
confidence: 99%
“…This means that VMS have an opportunity to volatilize to the air before being washed off during showering (Gouin et al, 2013 ; Montemayor et al, 2013 ). Other products, such as shampoos, conditioners, and shaving products, are likely to be washed off immediately and make a bigger contribution to the wastewater load (Franco & van Egmond, 2020 ). Monitoring data presented by van Egmond et al ( 2013 ) suggested that the Brooke et al ( 2009a ) estimate load estimates for D5 to wastewater (11.6 mg cap ⁻¹ day ⁻¹ ) may be overestimated by as much as a factor of 4.…”
Section: Emissionsmentioning
confidence: 99%